Improving Ability of Detecting Object Distance Through U-Qorselin Tools on Person with Visually Impaired - Marlina Marlina; Siti Qoniah (Journal of ICSAR, 2018)
This article discusses the improvement of the ability of the person of visually impaired in detecting object distance through the use of U-Qoserlin tools. This research used R & D method and continued with experiment. The subject of development experts consists of electrical engineering experts, orientation and mobility experts, and educational experts. The subject of the experiment consisted of five (5) the person of the visually impaired. The results of the study show that (1) U-Qoserlin tools are practical, feasible, useful and provide technological insights for the person of visually impaired; (2) the results of the data with the Mann Whitney test obtained the results of the smallest Uhit value is 9, and Utab at a significant level of 95% and α = 0.05 for n = 6 that is 5. Thus, U-Qoserlin tool effective in improving the ability to detect solid object spacing for the person of visually impaired. The implications of this study are that there should be a test of the effectiveness of U-Qoserlin on the number of the person of visually impaired more